Tracking the spatial patterns and thematic dynamics of GRACE satellite application over the last 20 years (2002–2022) - Zhang, Hongyue (Frontiers in Earth Science, 2024)
The GRACE (Gravity Recovery and Climate Experiment) satellite, operational from its launch in 2002 until October 2017, documented critical changes in global terrestrial water storage, significantly advancing the fields of gravity field analysis, hydrological variations, and environmental monitoring.This study investigates the thematic evolution of 2,966 SCIE-indexed publications on GRACE satellite applications from 2002 to 2022, utilizing co-occurrence network mapping and complex network analysis. Our results indicate a steady growth in GRACE satellite application research, with early publications (2002-2004) achieving an average citation rate exceeding 100, underscoring their substantial impact.